Exploration of new superconductors and functional materials, and fabrication of superconducting tapes and wires of iron pnictides. Issue 3 (8th May 2015) - Hosono, Hideo; Tanabe, Keiichi; Takayama-Muromachi, Eiji; Kageyama, Hiroshi; Yamanaka, Shoji; Kumakura, Hiroaki; Nohara, Minoru; Hiramatsu, Hidenori; Fujitsu, Satoru
Abstract: This review shows the highlights of a 4-year-long research project supported by the Japanese Government to explore new superconducting materials and relevant functional materials. The project found several tens of new superconductors by examining ∼1000 materials, each of which was chosen by Japanese experts with a background in solid state chemistry. This review summarizes the major achievements of the project in newly found superconducting materials, and the fabrication wires and tapes of iron-based superconductors; it incorporates a list of ∼700 unsuccessful materials examined for superconductivity in the project. In addition, described are new functional materials and functionalities discovered during the project.